Facing greenwashing accusations in fast fashion : how H&M group and Inditex communicate their commitments - Minelli, Laura (2024)
This research aimed to verify companies’ main communication strategies to deal with greenwashing accusations. To this extent, the methodology used was exploratory and qualitative. The primary objective of the thesis was to gain a deeper understanding of the challenges and opportunities associated with sustainable corporate practices in today’s business environment. By using content and comparative analysis, this study aimed to understand the relationship between corporate communication and greenwashing. The study analyses corporate communication, social responsibility, sustainability and greenwashing using online data from selected brands between 2019 and 2023. Sources include annual reports, official statements, corporate website announcements and sustainability reports. The analysed data showed that the corporate communication strategies used by H&M Group and Inditex to face greenwashing are focused on three main pillars: transparency, responsibility and circularity. In other words, these topics are used as a basis to avoid communication failures between its main stakeholders. There was also a clear balance between commitments and strategies to address the environmental, social and economic impacts of both parties, as well as an understanding of the need for innovation-driven evolution in the fashion business, collaboration and long-term goals. The transparency pillar reveals that Inditex and H&M Group emphasize how crucial it is to provide transparent, easily readable information about their performance and sustainability guidelines. However, there are differences between the two companies in how they approach this issue: while Inditex gives a high priority to openness, emphasizing governance frameworks, comprehensive reporting requirements and policy updates, the H&M Group emphasizes open communication with stakeholders and includes detailed progress updates, external audits and evaluations. The pillar of responsibility indicates that Inditex offers distinct commitments and scientific consistency, while the H&M Group emphasizes transformation. However, both companies have committed to achieving net zero carbon emissions by 2040, which is in line with international climate targets of keeping warming at 1.5°C (IPCC, 2015). The coordinated efforts highlight an understanding of the pressing need to address climate change and the need for structural transformation in the fashion sector. The circularity pillar shows that both companies highlight the importance of moving to a circular business model. The circular model is emphasized by H&M through its creative methods of sustainable design and materials. The company is committed to reducing its reliance on virgin materials and integrating circular design into products. Inditex, on the other hand, incorporates circularity into its commercial operations. The launch of Zara Pre-Owned is part of the company’s reported effort towards sustainability. However, both institutions are criticized for the lack of transparency regarding the management of clothing collected through their reuse programs and for the increase in production volumes. Both initiatives are part of its circular programs. In relation to their communication channels, Inditex and H&M Group present sustainability topics on their websites and reports, but the documents offer more specific techniques and information, while the sites focus on consumer awareness and stakeholder engagement. Regarding greenwashing, transparent collaboration and communication with stakeholders allow H&M Group and Inditex to share knowledge and develop innovative solutions that are crucial to tackle climate change, the management of resources and social responsibility, thus reinforcing a greater impact. The qualitative data indicated that a clear, efficient and comparable measurement technique is missing in the strategies of both companies. Especially for Inditex, the provision of information and transparency were considered insufficient.